Emerging a Novel VOPP1-EGFR Fusion Coexistent With T790M as an Acquired Resistance Mechanism to Prior Icotinib and Sensitive to Osimertinib in a Patient With EGFR L858R Lung Adenocarcinoma: A Case Report - Wang, Xia; Peng, Weiwei; Zeng, Zhimin; Cai, Jing; Liu, Anwen (Frontiers in Oncology, 2021)
Background: Epidermal growth factor receptor (EGFR) fusions are rare genomic events in non-small-cell lung cancer (NSCLC). Clinical support and evidence to guide management are absent for NSCLC patients harboring EGFR fusion. Case presentation: In this case report, we describe a 69-year-old female who received right lobectomy and was diagnosed with pathological stage IIIA lung adenocarcinoma harboring EGFR L858R. Twenty months later he had recurrent disease in the liver, lung, and bone, and was treated with icotinib. A novel vesicular overexpressed in cancer pro-survival protein 1 (VOPP1)-EGFR fusion gene coexistent with T790M were identified by next-generation sequencing using pericardial effusion and blood samples after icotinib treatment, which led to progression after icotinib six months and suggested a potential resistance mechanism. Subsequently, the patient was switched to osimertinib treatment, which resulted in a progression-free survival interval of more than 11 months. Conclusions: The present results suggested that acquired VOPP1-EGFR fusion gene with T790M potentially serve an additional resistance mechanism to first-generation EGFR tyrosine kinase inhibitors in EGFR-mutated NSCLC. And the present case increases the evidence supporting use of osimertinib for treatment of NSCLC patients harboring EGFR fusion.